Viscoelastic relaxation in a series of fluoropropylmethylsiloxane fluids - PŁOWIEC, Ryszard; KIM, Min Gon (Archives of Acoustics, 1978)
The paper presents the results of measurements of the shear impedance for samples of synthetic oil with different length of molecules for the shear frequencies 10, 30 and 450 MHz over a range of temperatures from –100°C do 50°C. It was found that the results of measurements of the shear impedance are well described by LAMB'S liquid model with the high-frequency approximation for the DAVIDSON-COLE term [...]. It has been shown that the coefficient 2K in this term is a function of the viscosity of the examined liquid. The results obtained have been interpreted as the superposition of two relaxation processes, one of high-frequency viscoelastic relaxation and one of low-frequency retardation related to the three-dimensional orientation of the molecules. The values of the individual relaxation times have been determined with the aid of ROUSE's theory.